LOBSTER: Local orbital projections, atomic charges, and chemical‐bonding analysis from projector‐augmented‐wave‐based density‐functional theory. Issue 21 (12th June 2020) - Nelson, Ryky; Ertural, Christina; George, Janine; Deringer, Volker L.; Hautier, Geoffroy; Dronskowski, Richard
Abstract: We present an update on recently developed methodology and functionality in the computer program Local Orbital Basis Suite Toward Electronic‐Structure Reconstruction (LOBSTER) for chemical‐bonding analysis in periodic systems. LOBSTER is based on an analytic projection from projector‐augmented wave (PAW) density‐functional theory (DFT) computations (Maintz et al., J. Comput. Chem. 2013, 34, 2557), reconstructing chemical information in terms of local, auxiliary atomic orbitals and thereby opening the output of PAW‐based DFT codes to chemical interpretation. We demonstrate how LOBSTER has been improved by taking into account time‐reversal symmetry, thereby speeding up the DFT and LOBSTER calculations by a factor of 2. Over the recent years, the functionalities have also been continually expanded, including accurate projected densities of states (DOSs), crystal orbital Hamilton population (COHP) analysis, atomic and orbital charges, gross populations, and the recently introduced k ‐dependent COHP. The software is offered free‐of‐charge for non‐commercial research. Abstract : The computer program LOBSTER for chemical‐bonding analysis in periodic systems has been updated. LOBSTER extracts local chemical information from PAW‐based DFT codes and now takes into account time‐reversal symmetry, thereby speeding up both DFT and LOBSTER calculations by a factor of 2. Besides accurate local DOS and COHP analysis, it also delivers atomic and orbital charges directly and rapidly from the wavefunction, in addition to the recently introduced k ‐dependent COHP.